Kerch Style Pelikai: Statistical Analysis of Morphology - Kolosov, Vladimir P.; Vas’ko, Dmitrii S. (Actual Problems of Theory and History of Art, 2021)
This research demonstrates the possibility of applying the modern statistical methods for analyzing the red-figure Kerch style pelikai dated back to the 4th century BC. Ninety-four vessels have been involved in analysis. Methods of geometric morphometry implemented in the computer programs Statisticа 8.0, tpsDig2 and MorphoJ were the basis of this study. The main goal of the research was to define the similarity of analyzed objects according to their morphological features. In the result, the main differences in proportions and shapes of vessels have been traced. It was proved that morphological features vary regardless of the pelikai absolute size. The most significant parameters have been determined and, according to these characteristics, patterns in the vessels differentiation as well as the data on their most common variants were obtained. The comparison of the morphological differences with the chronological data resulted in a general picture of the form transformation of the red-figure pelikai throughout the 4th century BC. The analysis showed that during the first half of the 4th century BC the relative height and smoothness of the vessel contours gradually increased. In the second half of the 4th century BC, pelikai acquired a relatively high throat and a low sharply curved upper part of body.
Keywords: statistical methods; red-figure pelikai; geometric morphometry